Pengembangan Algoritma Caesar Cipher dalam Game-Based Learning untuk Pendidikan Kriptografi pada Anak - Kesuma, Arya Dharma; Rahayuda, I Gede Surya (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
The decline in children's interest in learning caused by easy access to games is the main reason I designed game-based learning. As time goes by, the way of presenting learning material must also be changed to make it more interesting, interactive and can attract children's interest in learning. Games- Based learning is one way to answer this problem, with learning materials that are packaged attractively, it is hoped that it can increase children's interest in learning. In this game plan, it will introduce the world of IT to children, especially the world of cyber security. One of the concepts raised is cryptography. The algorithm used in this cryptography is the Caesar cipher because it is easy to understand and suitable for children. With a game design that is like a mystery and interactive, it is hoped that it can increase children's interest in learning and introduce cyber security.